Faktor yang Memengaruhi Financial Satisfaction Pengguna E-Commerce di Surabaya - Moch. Sigit Prabowo; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The use of the internet has now become a necessity in everyday life. E-commerce is the sale, purchase, marketing of goods or services through electronic systems or the internet. This study aims to determine the effect of financial literacy and financial attitude on financial management behaviour as a mediator for e-commerce users in Surabaya. The type of data used in this study is quantitative data and uses primary data. The number of samples used was 218 respondents with criteria for e-commerce users included in the top 10 e-commerce that dominated the Indonesian online market, residing in the city of Surabaya, and aged 18 to 35 years. This study's data collection instrument was the distribution of questionnaires online. The data analysis technique in this research uses the Path Analysis technique of the Complex Model using AMOS version 23. The results of this study are that financial literacy influences financial management behaviour. Financial attitude does not affect financial management behaviour because based on age that is still not fully able to manage their finances very well. Financial literacy and financial management behaviour affect financial satisfaction. Financial attitude does not affect financial satisfaction because respondents still do not have their income or their income level is not too high. Financial management behaviour mediates financial literacy for financial satisfaction. Financial management behaviour does not mediate financial attitude towards financial satisfaction.